Improved detection of gallbladder perforation by contrast-enhanced ultrasound: two case reports - Zhou, Yaxin; Yang, Lulu (Frontiers in Medicine, 2024)
Acute cholecystitis is a common acute abdominal disease, but the occurrence of secondary gallbladder perforation is relatively rare, and poses a serious threat to the lives of patientsand seriously threatens to the life of patients. The conventional methods for diagnosing acute cholecystitis are abdominal contrast-enhanced CT and ultrasound.However, these methods may have limitations in detecting gallbladder perforation, especially in cases where perforation size are small. In contrast, contrast-enhanced ultrasound (CEUS) has the distinct advantage of providing dynamic, real-time visualization of the gallbladder wall enhancement, thereby enabling a more confident diagnosis of gallbladder perforation. Here, we report two cases of acute cholecystitis initially diagnosed by abdominal contrast-enhanced CT, and secondary gallbladder perforation detected by further contrast-enhanced ultrasound. Both patients were finally treated in a timely manner. Our cases suggest that CEUS can be an important complementary method for diagnosing gallbladder perforation.